2008
DOI: 10.1103/physrevd.77.097702
|View full text |Cite
|
Sign up to set email alerts
|

Constraining walking and custodial technicolor

Abstract: We show how to constrain the physical spectrum of walking technicolor models via precision measurements and modified Weinberg sum rules. We also study models possessing a custodial symmetry for the S parameter at the effective Lagrangian level -custodial technicolor -and argue that these models cannot emerge from walking type dynamics. We suggest that it is possible to have a very light spin-one axial vector boson. However, in the walking dynamics the associated vector boson is heavy while it is degenerate wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 33 publications
3
34
0
Order By: Relevance
“…These new findings are compatible with the conjectured form of the beta function proposed in [7,8]; for recent extensions, see [11]. The models with higher representation matter fields have been shown to be compatible with the current precision data [5,14,15]. Their phenomenological implications for LHC experiments [16,17,18,19,20,21] as well as for cosmology [22,23,24] are being investigated.…”
Section: Introductionsupporting
confidence: 71%
“…These new findings are compatible with the conjectured form of the beta function proposed in [7,8]; for recent extensions, see [11]. The models with higher representation matter fields have been shown to be compatible with the current precision data [5,14,15]. Their phenomenological implications for LHC experiments [16,17,18,19,20,21] as well as for cosmology [22,23,24] are being investigated.…”
Section: Introductionsupporting
confidence: 71%
“…The effective theory contains composite scalars and spin-one vectors. Compatibility between the electroweak precision constraints and tree-level unitarity of W W -scattering was demonstrated in [64].…”
Section: Introductionmentioning
confidence: 97%
“…A key realization that enabled further progress was that gauge theories with fermions in two-index (symmetric or adjoint) representations of the underlying gauge group have interesting features [26,27,28,29,36], such as the possibility of the existence of a nonperturbative infrared fixed point for a very low number of flavors [26], naturally reducing the tension with precision data [26,36,37,38]. These properties make them intriguing candidates for walking technicolor type models [26,36] (related studies can be found in [39]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it is important to explore the consequences of this new constraint on composite models, in conjunction with those previously known from electroweak precision measurements. Given the recent evidence of the Higgs boson, a strongly interacting sector that is phenomenologically viable nowadays should include this scalar boson in its low energy spectrum, but it is also assumed that vector and axial-vector resonances should appear as well, in a way that the so called Weinberg sum rules [6] are satisfied [7][8][9].…”
Section: Introductionmentioning
confidence: 99%